AN ANALYSIS OF TASKS VOCABULARY IN ENGLISH TEXTBOOK “BAHASA INGGRIS X EDISI REVISI 2017” FOR SENIOR HIGH SCHOOL - Hatiarni Ode; Paula Hampp; Rinny Rorimpandey (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The study was done in the two purpose, first to describe types of task vocabulary that help students widen and deepen on their stock of vocabulary and second is to describe which type of vocabulary is the most dominant from textbook namely “Bahasa Inggris X edisi revisi 2017” for tenth grade in senior high school. In this study, quantitative content analysis was use because the data presented in the form of number or percentages. The source of data as in the textbook namely Bahasa Inggris x edisi revisi 2017. This study used descriptive analysis approach in analyzing the data. It means that this study was focus on tasks vocabulary found only in the textbook as written, not in general. The result shows: first, tasks vocabulary in the textbook consisted of two types: vocabulary builder and vocabulary exercise. Each of the types consisted of 16 tasks vocabulary. Thus, there were 32 tasks vocabulary in all. Second, tasks vocabulary that was the most dominant were sentence completion with 13 tasks (41%). What is interesting is that new words introduced in vocabulary builder section was repeated in a number of contexts: reading texts, reading comprehension questions, pronunciation section, vocabulary tasks, grammar tasks, and speaking tasks. This is in line with the principles of vocabulary learning: the Principle of Re-contextualization and the Principle of Multiple Encounters